1993
DOI: 10.2307/3350274
|View full text |Cite
|
Sign up to set email alerts
|

Segregation, Poverty, and Empowerment: Health Consequences for African Americans

Abstract: Cities in the United States have undergone major social transitions during the past two decades. Three notable factors in these shifts have been the development of a black political elite sustained rates of black poverty, and intensified racial segregation. Indications of the effect of these social forces on black-white differentials in health status have begun to surface in the research literature. This article reports analyses of data from all U.S. cities with a population of 50,000, at least 10 percent of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
153
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(158 citation statements)
references
References 48 publications
(31 reference statements)
5
153
0
Order By: Relevance
“…12,13 Studies examining the association between neighborhood SES and physiologic indicators of inflammation, including C-reactive protein, interleukin-6 (IL-6), 14 and serum albumin, 15 have found higher levels of 14,15 proinflammatory markers in residents of disadvantaged communities than in wealthier communities. 14,15 Black women at all levels of education are more likely to live in poor neighborhoods than are white women [16][17][18][19] ; thus, it is important to determine whether low neighborhood SES is associated with cardiovascular risk factors independent of individual-level SES. Previous studies of neighborhood SES and biomarkers that included black women were limited to low SES communities 5,20 and the elderly 21 or had too few subjects to allow for specific analyses of black women across SES.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Studies examining the association between neighborhood SES and physiologic indicators of inflammation, including C-reactive protein, interleukin-6 (IL-6), 14 and serum albumin, 15 have found higher levels of 14,15 proinflammatory markers in residents of disadvantaged communities than in wealthier communities. 14,15 Black women at all levels of education are more likely to live in poor neighborhoods than are white women [16][17][18][19] ; thus, it is important to determine whether low neighborhood SES is associated with cardiovascular risk factors independent of individual-level SES. Previous studies of neighborhood SES and biomarkers that included black women were limited to low SES communities 5,20 and the elderly 21 or had too few subjects to allow for specific analyses of black women across SES.…”
Section: Introductionmentioning
confidence: 99%
“…17,24,28 In addition to race/SES confounding, much of the health disparities research literature is likely biased because of racial segregation. 17,[29][30][31] The U.S. is a highly racially segregated society, whereby African Americans and whites have quite different health risk exposures. For example, Morland et al 32 found that compared with predominantly African-American neighborhoods, supermarkets were 2.9 times more likely to be located in racially integrated neighborhoods and 4.3 times more likely to be located in predominantly white neighborhoods.…”
Section: Introductionmentioning
confidence: 99%
“…And, several studies have demonstrated that African-American communities were more likely to be targeted for tobacco consumption compared to white communities. 36,37 Other studies have demonstrated a link between segregation and health disparities across a variety of unrelated health outcomes, such as infant mortality, 29,39,40 adult mortality, 30,[41][42][43] tuberculosis, 38,44 and hospital admissions. 45 However, segregation has not been well studied as a potential source of confounding, but it is potentially a substantial problem, which can lead to erroneous conclusions about the etiology of racial disparities in health.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Race as used in this article is a marker for relative social and economic advantage with respect to exposure to economic and noneconomic forms of racial discrimination that affect education, wealth, stability of employment, and health across the life course, [27][28][29] even among people living in neighborhoods with similar socioeconomic characteristics. [30][31][32] Some studies have shown that white populations have higher risks of homicide at lower levels of neighborhood socioeconomic conditions compared to black populations 33 ; yet other studies have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%